Chemical Classification of Corn Sheath Ash, Cassava Pulp Ash, and Granulated Blast Furnace Slag as Supplementary Cementitious Materials Using X-Ray Fluorescence Analysis (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Self-compacting concrete (SCC) enhances constructability through high flowability and self-consolidation; however, its elevated cement demand increases cost and environmental impact. This study evaluates Corn Sheath Ash (CSA), Cassava Pulp Ash (CPA), and Ground Granulated Blast Furnace Slag (GBFS) as partial cement replacements in SCC. Cement was replaced at levels of 0–20% by mass at a constant water-to-binder ratio of 0.50, following EFNARC guidelines. Workability was assessed using slump flow tests, while compressive strength was measured at 7, 14, and 28 days. Increasing replacement levels resulted in reduced flowability for all materials. At 20% replacement, slump flow decreased from 755 mm for the control mix to 662 mm and 645 mm for CSA- and CPA-based SCC, respectively, whereas GBFS mixes maintained higher flowability (≈684 mm). Compressive strength declined with increasing CSA and CPA content, with 28-day strengths reducing to 25.5 MPa and 21.3 MPa, respectively, due to cement dilution and limited reactivity. In contrast, GBFS-containing SCC achieved a 28-day compressive strength of approximately 29.1 MPa at 20% replacement, attributed to its latent hydraulic behavior. CSA and CPA are suitable up to 10–15% replacement, while GBFS can be used up to 20% to produce sustainable SCC.